Masalah Kelen bagaan Partai Politik di Indonesia Pasca-Orde Baru - Romli, Lili (Pusat Penelitian Politik, 2008)
In contemporary reform era political parties in Indonesia facing many problems. The public image of political party was not good due to their lack of capabilities to function well. This functional problem derived from the institutional problem of political parties. In this paper, there are three crucial institutional problems that have to be solved by political party: 1) ideology and platform; 2) cohesivity and conflict management; and 3) political recruitment and forming of cadres.